PENGEMBANGAN MEDIA FLIPBOOK DIGITAL BERBASIS AUGMENTED REALITY PADA MATERI KERAGAMAN BUDAYA INDONESIAKU KELAS V SEKOLAH DASAR - Dewa Gede Divayanha; Ni Putu Candra Prastya Dewi; Ni Nyoman Kurnia Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of technology has a significant impact on the world of education that can be used as an intermediary to achieve learning objectives and improve the learning process to be more interactive, this study was conducted with the aim of producing an interactive learning media in the form of a Digital Flipbook media based on Augmented Reality (AR) on the material